MALDI‐TOF‐CID for the microstructure elucidation of polymeric hydrolysable tannins. Issue 1 (25th June 2012) - Radebe, Nonhlanhla; Rode, Karsten; Pizzi, Antonio; Giovando, Samuele; Pasch, Harald
Abstract High molar mass wood tannin extracts are complex mixtures that are distributed in both molar mass and chemical composition. Hydrolysable tannins from tara, Turkey gall, and chestnut woods were analyzed and compared using matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectrometry. Although MALDI‐TOF MS reveals the oligomer structure of the tannins, this method cannot distinguish between isomers with isobaric masses and, therefore, ambiguous structural assignments were made in a number of cases. To determine the actual microstructures present, MALDI‐TOF‐CID (collision induced dissociation) experiments were conducted. MALDI‐TOF‐CID enables monomer sequence determination and positive assignments of isobaric structures can be made. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013